Magnet® Hospital Recognition Linked to Lower Central Line‐Associated Bloodstream Infection Rates. Issue 2 (25th January 2016) - Barnes, Hilary; Rearden, Jessica; McHugh, Matthew D.
Abstract: Central‐line‐associated bloodstream infections (CLABSI) are among the deadliest heathcare‐associated infections, with an estimated 12–25% mortality rate. In 2014, the Centers for Medicare and Medicaid Services (CMS) began to penalize hospitals for poor performance with respect to selected hospital‐acquired conditions, including CLABSI. A structural factor associated with high‐quality nursing care and better patient outcomes is The Magnet Recognition Program®. The purpose of this study was to explore the relationship between Magnet status and hospital CLABSI rates. We used propensity score matching to match Magnet and non‐Magnet hospitals with similar hospital characteristics. In a matched sample of 291 Magnet hospitals and 291 non‐Magnet hospitals, logistic regression models were used to examine whether there was a link between Magnet status and CLABSI rates. Both before and after matching, Magnet hospital status was associated with better (lower than the national average) CLABSI rates (OR = 1.60, 95%CI: 1.10, 2.33 after matching). While established programs such as Magnet recognition are consistently correlated with high‐quality nursing work environments and positive patient outcomes, additional research is needed to determine whether Magnet designation produces positive patient outcomes or rewards existing excellence. © 2016 Wiley Periodicals, Inc.